From Binary Perspectives to Context-Sensitive Approaches: Changing Trends in Scholarship on Political Islam in Turkey, Tunisia and Indonesia - Fuad, Ahmad Nur (Ulumuna, 2024)
This article deals with changing trends in scholarship on political Islam in Turkey, Tunisia, and Indonesia. Over the past decades, studies on political Islam have undergone significant changes, shaped by dynamic political contexts and theoretical frameworks. This article highlights changes in academic perspectives regarding political Islam within diverse global and national contexts. In Turkey, scholarship has shifted to analyzing interplays between secularism and political Islam under the Justice and Development Party (AKP). The post-Arab Spring in Tunisia has spurred academic investigations into the involvement of Ennahda with democracy and secular state institutions amid political instability. In Indonesia, scholars have examined various manifestations of political Islam represented by the Prosperous Justice Party (PKS) in the context of democratic processes. This article is a literature study, based primarily upon scholarly works on political Islam, it argues that scholarship on political Islam in the three countries witnesses changes, from binary narratives to more context-sensitive approaches, reflecting the evolutionary nature of political Islam in dynamic political landscapes. Initially perceiving political Islam as ideologically rigid, various studies now acknowledge the engagement of Islamist parties in democratic processes and their adaptation to gender issues, integration into transnational connections, and dynamic interplay with secularism. This article reveals that the moderation theory can be an analytical tool for scrutinizing changing trends in studying political Islam.